2004
DOI: 10.1016/j.pain.2003.12.017
|View full text |Cite
|
Sign up to set email alerts
|

The cyclooxygenase isozyme inhibitors parecoxib and paracetamol reduce central hyperalgesia in humans

Abstract: Non-steroidal antiinflammatory drugs (NSAIDs) are known to induce analgesia mainly via inhibition of cyclooxygenase (COX). Although the inhibition of COX in the periphery is commonly accepted as the primary mechanism, experimental and clinical data suggest a potential role for spinal COX-inhibition to produce antinociception and reduce hypersensitivity. We used an experimental model of electrically evoked pain and hyperalgesia in human skin to determine the time course of central analgesic and antihyperalgesic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
0
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(77 citation statements)
references
References 42 publications
5
67
0
5
Order By: Relevance
“…Here the ongoing pain was unaffected, whereas the hyperalgesia was decreased [43]. The ongoing pain was assessed by subjective ratings and the limited sensitivity of this measuring method is in consensus with findings of Bromm et al [38,44].…”
Section: Dosing Regimessupporting
confidence: 53%
See 1 more Smart Citation
“…Here the ongoing pain was unaffected, whereas the hyperalgesia was decreased [43]. The ongoing pain was assessed by subjective ratings and the limited sensitivity of this measuring method is in consensus with findings of Bromm et al [38,44].…”
Section: Dosing Regimessupporting
confidence: 53%
“…Compared with NSAIDs, paracetamol has a different mechanism of action with less affinity to the peripheral cyclooxygenases and a more pronounced central effect, and this could explain the different findings for, for example, the cold pressor test and freeze lesion [32,42,46,47]. Furthermore, this is supported by findings in the continuous electrical hyperalgesia model, which probably activates central mechanisms that were attenuated by paracetamol [44]. However, NSAIDs also demonstrate effect towards central hyperalgesic mechanisms [15,22].…”
Section: Mechanistic Aspectsmentioning
confidence: 99%
“…The COX-2 isoform appears to be the enzyme responsible for inflammation and pain. COX-2 inhibitors, such asparecoxib, reduce secondary hyperalgesia and appear to reduce central sensitization in humans [38,39]. Celecoxib (the only COX-2 inhibitor approved in the North American marketplace) has demonstrated a reduction in postoperative pain, a reduced need for postoperative opioid analgesia [40], and did not inhibit bone healing following arthroplasty surgery [41].…”
Section: Non-steroidal Anti-inflammatory Drugs (Nsaids)mentioning
confidence: 99%
“…Several studies [16,17] have shown COX-2 in the spinal dorsal horn could modulate spinal nociceptive processes. Furthermore, epidural parecoxib reportedly has no neurotoxicity in rats over 21 days [15].…”
Section: Discussionmentioning
confidence: 99%
“…Intravenous use of a COX-2 antagonist may inhibit the systemic inflammatory response and prostaglandin synthesis, relieve inflamed peripheral tissues, and consequently provide pain relief [26]. Two studies showed that COX-2 in the spinal dorsal horn could modulate spinal nociceptive processes and is associated with antihyperalgesia in the central nervous system [16,17]. Therefore, we postulated that applying a COX-2 antagonist directly to the peripheral nerve might reduce the COX-2 activation and down-regulate pain intensity.…”
mentioning
confidence: 98%